Testing Of Economic Convergence In The Middle Of The Covid-19 Pandemic - samsul arifin; Sayifullah Sayifullah (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2021)
This study aims to see whether the process of export and import convergence occurs with the control variable of the size of the country's economy affected by the COVID-19 pandemic as measured by GDP and spatial interactions. The method of analysis in this study uses the Spatial Dynamic Panel. The research objects are 64 countries affected by the COVID-19 pandemic—data taken in the period 2019q4-2020q3. The results show that GDP and spatial elements influence the process of export and import convergence. The speed of convergence and the length of time to reach a steady-state, imports are better than exports reaching 28-38% with about one semester and reaching 15-16% with a duration of 1 year (export model). Exports and imports during the COVID-19 pandemic reflect interactions between countries, with distance as a determining factor. However, the role of interaction between countries tends to be insignificant in the long run.